Association between carbohydrate and fat intake and estradiol levels with body fat percentage in Minangkabau ethnic premenopausal women, in Padang City West Sumatra year 2018 - Natan, Okdi; Lestari, Yuniar; Arysanty, Dessy; Sulastri, Delmi (International Journal of Research in Medical Sciences, 2019)
Background: Excessive carbohydrate and fat intake with excess estradiol levels will cause an increase in body fat percentage, thus causing obesity in premenopausal women. Objective was to determine the association between carbohydrate intake with fat percentage, the association between fat intake with fat percentage, the association between SAFA intake with fat percentage, the association between MUFA intake with fat percentage, the association between PUFA intake with fat percentage, and the association between estradiol levels with fat percentage in Minangkabau ethnic premenopausal women in Padang City, West Sumatra. Methods: This research was carried out in Padang City. Research conducted was observational research with cross sectional research design. Subjects in this research were 52 people. Variables in body fat percentage were measured using Bioelectrical Impedance Analysis (BIA), carbohydrate and fat intake data were obtained by interviewing the Food Frequency Questionnaire (FFQ), and estradiol levels were examined by ELISA. Data analysis was performed using Pearson correlation test. Results: In premenopausal women in the city of Padang, low carbohydrate intake was found with an average of 227.25grams, high fat intake was found with an average of 77.84grams, high SAFA intake was found with an average of 27.59grams, low MUFA intake was found with an average of 9.91grams, normal PUFA intake was found with an average of 9.37grams, normal estradiol levels was found with an average of 145.95pg/ml, and more fat percentage was found with an average of 33.31. Conclusions: There was an association between carbohydrate intake with fat percentage, there was an association between fat intake with fat percentage, there was an association between SAFA intake with fat percentage, there was an association between MUFA intake with fat percentage, there was an association between PUFA intake with fat percentage, and no association between estradiol levels with of fat percentage in premenopausal women in Padang City.